An overview of different methods to establish a murine premature ovarian failure model - Negar Pouladvand; Mahnaz Azarnia; Hadis Zeinali; Rouhollah Fathi; Somayeh Tavana (Animal Models and Experimental Medicine)
Abstract Premature ovarian failure (POF)is defined as the loss of normal ovarian function before the age of 40 and is characterized by increased gonadotropin levels and decreased estradiol levels and ovarian reserve, often leading to infertility. The incomplete understanding of the pathogenesis of POF is a major impediment to the development of effective treatments for this disease, so the use of animal models is a promising option for investigating and identifying the molecular mechanisms involved in POF patients and developing therapeutic agents. As mice and rats are the most commonly used models in animal research, this review article considers studies that used murine POF models. In this review based on the most recent studies, first, we introduce 10 different methods for inducing murine POF models, then we demonstrate the advantages and disadvantages of each one, and finally, we suggest the most practical method for inducing a POF model in these animals. This may help researchers find the method of creating a POF model that is most appropriate for their type of study and suits the purpose of their research.